Acetone extract of Flammulina velutipes caps: A promising source of antioxidant and anticancer agents - Ukaegbu, Chinonso Ishmael; Rashid, Shah Samiur; Hazrulrizawati, Hamid; Alara, Oluwaseun Ruth (Elsevier, 2018)
The high death rate associated with cancer has fuelled the search for complementary cancer treatment methods in recent times. Among the leading alternative methods is natural products which have attracted much attention due to their high body tolerance. In this study, the caps of Flammulina velutipes (commonly called Enoki), an edible mushroom, were extracted with different solvents and characterized for in vitro antioxidant and anticancer activities. The anticancer activity of the extract was studied against breast cancer cells (MCF-7 and MDAMD-231) and normal or Vero breast cells (MCF-10a). The radical scavenging, metal reducing power, and anticancer properties of the extracts were investigated via in vitro chemical and cell-based methods. Furthermore, a phytochemical profiling process was performed on the extract fraction with the highest level of biological activities using Liquid chromatography-mass spectrometry coupled with quadrupole time of flight (LC-MS-QTof). The results showed acetone fraction of Enoki caps to exhibit more radical scavenging activity against 2,2-diphenyl- 1-picrylhydrazyl (DPPH) free radicals (IC50=0.840 mg/mL) and hydrogen peroxide (H2O2) radicals (IC50=0.890 mg/mL) compared to the ethyl acetate fraction (IC50=0.97 mg/mL against DPPH and 1.180 mg/ mL against H2O2). Additionally, acetone fraction showed a better metal reducing property in a concentration-dependent manner. The in vitro cytotoxicity study showed a preferential level of toxicity of the acetone extract to the studied cancer cell lines compared to the Vero cells. This extract showed more cytotoxicity against MCF-7 (IC50 value ranged from 17.7 μg/mL to 38.36 μg/mL) and MDA-MB-231 (IC50 value ranged from 114.5 μg/mL to 184.2 μg/mL) compared to MCF-10a (> 250 μg/mL). These findings present F. velutipes caps as a potential natural source of antioxidant and anticancer agents.